Mensmaven, a Fashion Blog and Thrift Store - Divyansh Srivastava; Preeti Singh; Alka Singh; Jai Srivastava (International Journal of Information Security Engineering, 2023)
Mensmaven is a fashion and lifestyle content creator, reaching thousands of men and women every month through social media efforts. Mensmaven covers topics including menswear, lifestyle, grooming, and fitness. It is a blog-based website that gives practical style tips as well as approachable, honest, and relatable content for everyday men who are interested in menswear. A thrift store has also been created, which is a terrific place to get resale high-end goods and accessories at a fraction of the retail price.
Keywords: Men's fashion; craftsmanship; grooming; lifestyle; thrift store